2017
DOI: 10.21595/jve.2015.16303
|View full text |Cite
|
Sign up to set email alerts
|

Investigation the accuracy of FEMA-440 procedure to analyze soil-structure systems

Abstract: A common analysis method of soil-structure systems in seismic design procedures such as FEMA-440 is to replace the entire soil-structure system by a fixed-base oscillator with an equivalent fundamental period and damping ratio to consider inertial effect of soil-structure interaction. It is generally believed by researchers that ignoring kinematic effect of soil-structure interaction is conservative to determine response of structures and FEMA-440 supports this idea by defining a reduction factor applying to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…The non-linear nature at the interface of structure and soil is also considered. Khanmohammadi, L. et al [10] performed the analysis in the time domain. The frequency domain considers only linear behaviour.…”
Section: Methods Of Analysis Of Ssi Problemsmentioning
confidence: 99%
“…The non-linear nature at the interface of structure and soil is also considered. Khanmohammadi, L. et al [10] performed the analysis in the time domain. The frequency domain considers only linear behaviour.…”
Section: Methods Of Analysis Of Ssi Problemsmentioning
confidence: 99%
“…In particular, FEMA 440 considers the reducing effect of kinematic interaction by modifying a free-field response spectrum or time history suite to estimate FIMs ( 27 ). However, it should be pointed out that some studies found that the rocking components of FIM may increase the structural demands and lead to non-conservative designs for soil-structure systems with deep embedded foundations ( 28 , 29 ). Since the primary objective of this study is to investigate the beneficial effect of using LRB isolators for bridge seismic retrofit, FFMs at foundation levels are used as input motions by ignoring that the foundation would alter the incoming ground motion because of its inherent stiffness and ground motion incoherence.…”
Section: Evaluation Of Input Ground Motionmentioning
confidence: 99%